Penggunaan Assesment For Learning Berbasis Comment Only Marking Terhadap Hasil Belajar Kognitif Siswa : (Use of Comment Only Marking Based Assessment for Learning on Student Cognitive Learning Outcomes) - Hana Nurul Karimah; Sistiana Windyariani; Himatul Aliyah (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
The assessment is very important because it can express information on learning outcomes as a whole and continuously that can be used as a reference to determine student achievement and cognitive abilities. One of the assessments emphasized in the 2013 curriculum is the authentic assessment with the characteristics of assessment for learning and assessment of learning. The results of observations indicate the use of assessment is still dominated by the assessment of learning that is giving a score only. Assessment for learning based on comment only marking is an assessment of not only scores but students get follow-up from comments given as feedback. The study aims to determine the effect of assessment only learning based on comment only marking on cognitive learning outcomes of class XI students of the State Senior High School in Sukabumi Regency on the material regulatory system which was carried out on the 2nd and 3rd week of April 2020. This study used a pre- experimental and using one-group pretest-postest design. Samples were taken by purposive sampling technique totaling 36 students. The research instrument was in the form of cognitive test questions and student response questionnaires. The test questions used are cognitive tests based on Bloom's revised taxonomy with indicators C1 (remembering), C2 (understanding), C3 (applying), C4 (analyzing), C5 (evaluating), and C6 (creating) consisting of 30 multiple choice questions . The student response questionnaire used amounted to 30 statements with the types of negative and positive statements. Data analysis refers to the provisions of the category of cognitive abilities based on the 0-100 scale Ministry of Education and Culture with very good, good, enough, and less categories. The data obtained that as many as 86% of students get cognitive learning outcomes with very good categories, 92% of students complete learning and 83% of students give positive responses to the use of assessment for learning based on comment only marking. The results of this study indicate that there is an influence on the use of assessment only learning based on comment only marking on the cognitive learning outcomes of high school students in the material system of human regulation. Abstrak. Penelitian ini dilakukan berdasarkan temuan dari hasil observasi yaitu masih banyaknya hasil belajar kognitif siswa yang belum mencapai ketuntasan KKM, hal tersebut disebabkan siswa tidak mengetahui kekurangan dan kelebihan dari pengetahuan yang mereka miliki. Hal tersebut karena penilaian yang diberikan guru didominasi oleh penilaian sumatif yaitu penilaian yang diberikan hanya berupa skor dan tidak memberikan feedback. Dengan demikian, diperlukan suatu strategi penilaian untuk meningkatkan hasil belajar kognitif siswa, yaitu dengan penilaian formatif yang disebut juga dengan Assesment for Learning. Comment Only Marking (COM) merupakan salah satu elemen dari strategi AfL. Tujuan penelitian ini yaitu untuk mengetahui pengaruh Assesment for Learning berbasis Comment Only Marking terhadap hasil belajar kognitif siswa kelas XI SMA pada materi sistem regulasi. Penelitian ini menggunakan metode pra-eksperimen (Pre-Eksperimental) dan menggunakan One-Group Pretest-Postest Design. Adapun populasi pada penelitian ini yaitu kelas XI SMAN 1 Cisaat, sampel dalam penelitian ini yaitu kelas XI IPA 3 yang terdiri dari 36 siswa dengan teknik purposive sampling. Instrumen penelitian yang digunakan untuk mengumpulkan data yakni berupa tes dan angket respon siswa. Dari hasil penelitian diperoleh nilai rata-rata hasil belajar kognitif siswa pada saat pretest sebesar 71,11 dan posttest sebesar 90,06 serta 92% siswa dinyatakan tuntas KKM. Respon siswa menunjukkan sebanyak 83% siswa memberikan respon positif dan 17% siswa memberikan respon negative terhadap penggunaan AfL berbasis COM. Uji hipotesis dengan Wilcoxon memperoleh Asymp. Sig. (2-tailed) bernilai 0,000, maka dalam penelitian ini H0 ditolak dan H1 diterima. Pada penelitian ini dapat disimpulkan bahwa terdapat pengaruh dari penggunaan Assesment for Learning berbasis Comment Only Marking terhadap hasil belajar kognitif siswa SMA pada materi sistem regulasi manusia. Kata Kunci : Assessment for Learning, Comment Only Marking, Hasil Belajar Kognitif.